Survival benefit with IMRT following narrow‐margin hepatectomy in patients with hepatocellular carcinoma close to major vessels. (3rd June 2015) - Wang, Wei‐Hu; Wang, Zhi; Wu, Jian‐Xiong; Zhang, Tao; Rong, Wei‐Qi; Wang, Li‐Ming; Jin, Jing; Wang, Shu‐Lian; Song, Yong‐Wen; Liu, Yue‐Ping; Ren, Hua; Fang, Hui; et al.
Abstract: Background & Aims: To investigate the role of post‐operative intensity‐modulated radiotherapy (IMRT) in patients receiving narrow‐margin hepatectomy for hepatocellular carcinoma (HCC) located close to the major vessels. Methods: This exploratory study involved 181 HCC patients. Of them, 116 were treated with narrow‐margin (<1.0 cm) hepatectomy. Thirty‐three of the 116 underwent postoperative IMRT (Group A), while 83 did not receive radiotherapy (Group B). The remaining 65 patients underwent wide‐margin (≥1.0 cm) hepatectomy (Group C). Prognosis and patterns of recurrence were assessed in the three groups. Results: The 3‐year overall survival (OS) and disease‐free survival (DFS) rates were 89.1 and 64.2% in Group A, 67.7 and 52.2% in Group B and 86.0 and 60.1% in Group C respectively. The OS and DFS of Group A and Group C patients surpassed those of Group B patients (Group A vs. B, P = 0.009 and P = 0.038; and Group C vs. B, P = 0.002 and P = 0.010). Patients in Groups A and C experienced significantly fewer early recurrences than did patients in Group B ( P = 0.002). Furthermore, patients in Groups A and C experienced substantially fewer intrahepatic marginal ( P = 0.048) and diffuse recurrences ( P = 0.018) and extrahepatic metastases ( P = 0.038) than did patients in Group B. No patient developed radiation‐induced liver disease. Conclusions: Post‐operative IMRT following narrow‐margin hepatectomy may be a favourable therapy for both its safety profile and clinical benefit in patients with HCC located close to the major vessels.